Once a rancher ebook - Miller, Linda Lael (The Carsons of Mustang Creek, 2023)
From a New York Times– bestselling author, “[a] marvelous contemporary western trilogy launch . . . fraught with amazing chemistry” ( Publishers Weekly ). The Carsons of Mustang Creek: three men who embody the West and define what it means to be a rancher, a cowboy and a hero in this brand-new series from the queen of Western romance Slater Carson might be a filmmaker by trade, but he’s still a cowboy at heart—and he knows the value of a hard day’s work under the hot Wyoming sun. So when he sees troubled teen Ryder heading down a dangerous path, he offers the boy a job on the ranch he shares with his two younger brothers. And since Ryder’s guardian is the gorgeous new Mustang Creek resort manager, Grace Emery, Slater figures it can’t hurt to keep a closer eye on her, as well . . . Grace Emery doesn’t have time for romance. Between settling into her new job and caring for her ex-husband’s rebellious son, her attraction to larger-than-life Slater is a distraction she can’t afford. But when an unexpected threat emerges, she’ll discover just how far Slater will go to protect what matters most—and that love is always worth fighting for. “Linda Lael Miller creates vibrant characters and stories I defy you to forget.” —Debbie Macomber, #1 New York Times– bestselling author of The Best is Yet to Come